Good Soldiering and Re-Virtuing Military Ethics Training - Cronshaw, Darren (International journal of public theology, 2022)
With warfare’s increasing complexity and damage from ethical failures, it is critical for defence forces to develop best practice training in military ethics. As the Australian Army’s Good Soldiering program suggests, soldiers require technical but also ethical competence. But how are ethical behaviours and the virtues they depend on cultivated in soldiers and how can chaplains contribute as public theologians? Military ethics education includes teaching just war principles of Laws of Armed Conflict, as well as understanding illegal orders and command responsibility. But ultimately ethical behaviour, following Aristotle, is grounded in character development and best informed by a revival of virtue ethics. Case studies are a training format which cultivate virtues and their application. Military ethics training at its best is virtue-based and practiced with simulated dilemmas in order to equip soldiers to act justly and exercise ‘good soldiering’ in the home, barracks, field and operations.